STRATEGI DIGITAL UMKM UTAMA VEGETARIAN: PENGEMBANGAN SITUS WEB UNTUK PEMASARAN GLOBAL - Yuwono, Wisnu; Putra, Sandy (ICON Publisher, 2025)
This community service project aims to develop a website that can enhance the digital presence and support the market expansion of Utama Vegetarian, a small business that provides high-quality vegetarian food products. The implementation method consists of three main stages: needs analysis, website development using the Wix platform, and training the partner to manage the website independently. The analysis techniques used include semi-structured interviews and direct observations of the business operations to understand the challenges faced by the partner in expanding market reach and managing brand identity. Additionally, secondary data collection was also carried out to assess global trends in the vegan food industry, which supports the development of more effective digital marketing strategies. The outcome of this project is the creation of a user-friendly website with features such as a product catalog, educational articles, and e-commerce integration, which can enhance customer interaction and expand the market of Utama Vegetarian both locally and internationally. Furthermore, the partner now has a practical guide and the skills to manage the website independently, supporting the sustainability and future development of the business. Additionally, the website is designed with features ready for further development, including analytics integration and international payment options, enabling broader expansion into the global market.